Personal-data disclosure in a field experiment: Evidence on explicit prices, political attitudes, and privacy preferences - Joachim Plesch; Irenaeus Wolff (Games, 2018)
Many people implicitly sell or give away their data when using online services and participating in loyalty programmes-despite growing concerns about company's use of private data. Our paper studies potential reasons and co-variates that contribute to resolving this apparent paradox, which has not been studied previously. We ask customers of a bakery delivery service for their consent to disclose their personal data to a third party in exchange for a monetary rebate on their past orders. We study the role of implicitly and explicitly stated prices and add new determinants such as political orientation, income proxies and membership in loyalty programmes to the analysis of privacy decision. We document large heterogeneity in privacy valuations, and that the offered monetary benefits have less predictive power for data-disclosure decisions than expected. However, we find significant predictors of such decisions, such as political orientation towards liberal democrats (FDP) and membership in loyalty programmes. We also find suggestive evidence that loyalty programmes are successful in disguising their 'money for data' exchange mechanism.
Keywords: C93; D19; D91; 330; data protection; data privacy; explicit prices; information economics; consumer behaviour; personal data; field experiment